Republic of Mozambique : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2007)
This Selected Issues paper on the Republic of Mozambique reports key policy and institutional issues in the macroeconomic management of scaled-up aid and in promoting sustainable private-sector led growth. A further moderate scaling-up of foreign aid could continue to be fully spent and focus on productive priority sectors. This would help achieve the Millennium Development Goals while at the same time eliciting a supply response to mitigate potential Dutch-disease effects brought on by an appreciating real exchange rate.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet